Influence of mercuric chloride and sodium hypochlorite on apical and axillary buds regeneration of Colocasia esculenta in tissue culture (2018). American Journal of Biotechnology and Bioscience - CACAÏ, Gilles Habib Todjro (My University, 2018)
Taro (Colocasia esculenta L. SCHOTT) is a staple food in many southern countries and an ancient starchy crop consumed by more than 400 million people. It is treated by diseases and pests that affect seed availability. Thus, the techniques of in vitro culture mostly used to overcome the problem of seeds production meet enormous difficulties of infection and necrosis of the explants. This study aims to determine the optimal use of mercuric chloride and sodium hypochlorite for disinfection of apical and axillary buds of taro. For this purpose, three doses of sodium hypochlorite (8%, 10% and 12%) and mercuric chloride (0.08%, 0.1% and 0.15%) were used with three immersion times ( 25 min, 30 min and 45 min) for sodium hypochlorite and (5min, 7min and 10min) for mercuric chloride. A binary logistic analysis was performed to understand or predict the effect of different doses of NaOCl and HgCl2 on the behavior of apical and axillary buds of taro. The results showed that 8% sodium hypochlorite with immersion time of 25 minutes is favorable for the disinfection of both apical and axillary explants of taro. For mercuric chloride, only the dose of 0.15% is effective for apical bud survival. The present study offers an opportunity to make available the seed of taro through the organogenesis of the species without any risk of infection.
Keywords: Colocasia esculenta; in vitro; desinfection